Between Innovation and Dogmatism: ‘Party Economic Functionaries’ as an Actors of Interaction between Regions and Center in Context of Transformation of Socio-Economic Sphere of USSR in 1970s — Early 1980s - Yu. S. Nikiforov (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
The ideas of heads of Soviet enterprises from different regions of the country concerning the socio-economic development of the USSR, expressed at a meeting in Moscow in 1983, are analyzed. The socio-psychological characteristics that were inherent in the Soviet economic leaders at the regional level, who were involved in discussing the problems of ‘improving the economic mechanism’, are studied in detail. The source base of the study includes documents from the Russian  State  Archive of Socio-Political History and the Center for Documentation of the Recent History of the Yaroslavl Region, oral history data (interviews with representatives of the regional authorities of the 1970s-1980s, which were personally conducted by the author of the article) and scientific literature. It is argued that the opinions of directors of the largest enterprises were perceived by party officials with the same level of trust as the opinions of representatives of the scientific community. It is concluded that the ideas of the party and economic activists intertwined the innovative nature of thinking with the dogmatic patterns of Soviet ideology. It is noted that the activities of the party and economic activists contributed to the formation of a kind of proto-bourgeoisie in the USSR in the 1970s-1980s. It is emphasized that the ideas of the party active on expanding the rights of enterprises and material incentives were a manifestation of latent capitalist tendencies. It is concluded that the main factor in the effective interaction of the regional ‘party economic functionaries’ with Moscow was close informal relations.